International cooperation in the field of regulation of aggressive tax planning - Melnyk, Yu. O.; Мельник, Ю. О.; Мельник, Ю. О. (Одеса : Гельветика, 2019)
The article is devoted to the research of international cooperation in the field of regulation of aggressive tax planning. Main initiatives in the sphere of the tax planning limitation were researched, the BEPS as the key international initiative was studied and the preconditions of implementation of the BEPS actions in Ukraine were identified.

Міжнародне співробітництво в галузі регулювання агресивного податкового планування. Стаття присвячена дослідженню міжнародного співробітництва в галузі регулювання агресивного податкового планування. Досліджено основні ініціативи в сфері обмеження податкового планування, вивчені BEPS як ключова міжнародна ініціатива і визначено передумови реалізації заходів BEPS в Україні.

Международное сотрудничество в области регулирования агрессивного налогового планирования. Статья посвящена исследованию международного сотрудничества в области регулирования агрессивного налогового планирования. Исследованы основные инициативы в сфере ограничения налогового планирования, изучены BEPS как ключевая международная инициатива и определены предпосылки реализации мероприятий BEPS в Украине.
Melnyk Yu. O. International cooperation in the field of regulation of aggressive tax planning / Yu. O. Melnyk // Актуальні проблеми держави і права : зб. наук. пр. Вип. 82 / редкол.: В. В. Завальнюк (голов. ред.) та ін. – Одеса : Гельветика, 2019. – С. 128-133.
Keywords: BEPS; tax planning; Common Reporting Standard; international corporation; BEPS; податкове планування; Common Reporting Standard; міжнародна корпорація; BEPS; налоговое планирование; Common Reporting Standard; международная корпорация